Gadus morhua Eggs Sialoglycoprotein Prevent Estrogen Deficiency-Induced High Bone Turnover by Controlling OPG/RANKL/TRAF6 Pathway and Serum Metabolism - Zhao, Meihui; Mei, Fengfeng; Lu, Jinfeng; Xiang, Qingying; Xia, Guanghua; Zhang, Xueying; Liu, Zhongyuan; Zhang, Chenghui; Shen, Xuanri; Zhong, Qiuping (Frontiers in Nutrition, 2022)
In recent years, the development of safe and effective anti-osteoporosis factors has attracted extensive attention. In this study, an estrogen-deficiency osteoporosis rat model was employed to study the improving mechanism of sialoglycoprotein isolated from Gadus morhua eggs (Gds) against osteoporosis. The results showed that compared with OVX, Gds ameliorated the trabecular microstructure, especially the increased trabecular thickness, decreased trabecular separation and enhanced the trabecular number. The analysis of qRT-PCR and western blotting found that Gds reduced bone resorption by inhibiting RANKL induced osteoclastogenesis. The LC-MS/MS was used to investigate serum metabolism and the enrichment metabolites were analyzed by the KEGG pathway. The results revealed that the Gds significantly altered the fat anabolism pathway, including ovarian steroidogenesis pathway and arachidonic acid metabolism pathway. Altogether, Gds could improve osteoporosis by suppressing high bone turnover via controlling OPG/RANKL/TRAF6 pathway, which is implicated with ovarian steroidogenesis pathway and arachidonic acid metabolism pathway. These findings indicated that Gds could be a candidate factor for anti-osteoporosis.